Waterborne copper impairs grazer‐induced colony formation and photosynthetic efficiency in Scenedesmus obliquus. (14th December 2015) - Huang, Yuan; Nan, Haihong; Zhu, Xuexia; Li, Bangping; Zhang, Zeng; Yang, Zhou
Abstract: Grazer‐induced defense in phytoplankton is known to stabilize community dynamics within aquatic environments. Metal contamination in waters is of grave concern worldwide due to its cytotoxicity to organisms. With the aim of elucidating grazer‐induced defense responses in metal (Cu)‐contaminated waters, we grew the alga Scenedesmus obliquus in media with or without Daphnia filtrate at different concentrations of free Cu 2+ (0.03–23.3 × 10 −3 μ mol L −1 ). In the presence of Daphnia filtrate, S. obliquus cultured in healthy conditions (0.03 × 10 −3 μ mol L −1 free Cu 2+ ) was comprised of 60.4% eight‐celled colonies, with 3.4 cells per particle on average on day 3. At Cu 2+ concentrations higher than 2.91 × 10 −3 μ mol L −1, algal growth and photosynthetic efficiency decreased along with reduction in the proportions of colonial populations. Exposure to ≤ 0.89 × 10 −3 μ mol L −1 free Cu 2+ had no significant effect on algal growth and photosynthesis; however, the ability of S. obliquus to form colonies in response to Daphnia filtrate was impaired. These results suggest high sensitivity of grazer‐induced morphological defense to Cu toxicity in Scenedesmus . Metal contamination may result in inducible defended algae being easily grazed by small herbivores, potentially changing the energy flow along the food chain in contaminated waters.